Extracting Patterns from Students’ Feedback using Mixed Method - Shanta Kumar, TH (International Journal of Computer Sciences and Engineering, 2025)
It is common practice to collect feedbacks from the students in order to evaluate the performance of their teachers. Questionnaire is one of the best ways of collecting this information. Analysis of this questionnaire is crucial and not easy especially if it contains both quantitative and qualitative measures. This paper provides a comprehensive analysis of students’ evaluation of faculties’ teaching Computer Science at GIMT. The 5-points scale being used in quantitative analysis is being converted to 2-points scale and is supplemented by result from the qualitative analysis.